Factors Related to Female Adolescent Parents’ Acceptance of the Human Papillomavirus Vaccine - Dora Samaria; Nevin Zhasmin Mizka (Jurnal Kesehatan Komunitas (Journal of Community Health))
The government of Indonesia instructs the Human Papillomavirus (HPV) vaccine to be a mandatory vaccine for young women in Indonesia. The HPV vaccine effectively protects against HPV infection by HPV types 16 and 18, which are responsible for more than 70% of cervical cancers. There are challenges in the implementation of HPV vaccination related to parental acceptance. This study aims to determine the factors that influence the acceptance of parents of young women to the HPV vaccine in the Pejuang Public Health Center area. This research performed a cross-sectional design with 197 parents or guardians of young women domiciled in the Pejuang Public Health Center area who were selected using consecutive sampling. Data analysis utilized the Chi-Square, Mann-Whitney, Independent T, and Multiple Logistic Regression with Backward Method tests. The results revealed that only three variables had a significant relationship with acceptance of the HPV vaccine with an odds ratio of knowledge (OR=3.01, p=0.000), attitude (OR=4.76, p=0.000), and health literacy (OR = 2.15, p=0.016). The results of multivariate analysis disclosed that the most influential factor in acceptance of the HPV vaccine was attitude (OR=4.41, p=0.00). This study concluded factors that influenced parents’ acceptance of the HPV vaccine were knowledge, attitude, and health literacy, with the most influencing factor being attitude. Efforts to socialize the benefit of the HPV vaccine in the parental community are suggested to improve the attitudes of young women's parents to support their daughters in getting the HPV vaccine.